CRIMINAL LAW FORMULATION AGAINST UNDERAGE CHILD MARRIAGE - Huda, Mohammad Nurul; Saadah, Khulasotun Nuroiyah Ummi; Silva, Cristovao Adao Da; wahyudi, Wahyudi (TRUNOJOYO LAW REVIEW, 2023)
The phenomenon that is developing in Indonesia today, especially in rural communities where the continuity of marriage is vulnerable to minors. This happens due to 2 (two) factors, namely internal and external. This type of research uses normative juridical methods and the approach to theproblemuses 2 (two) kinds of approaches. First, through a statutory approach, namely by examining laws and regulations related to legal issues or problems being studied, isthere any suitability and consistency between the law and other laws. Second, the Conceptual Approach, the conceptual approach departs from the views and doctrines that develop in the science of law. Children are an investment for every country in the world, because they are future human resources for the development of a country. Juridically, each State is responsible for providing a good life for children, providing welfare both physically and mentally, and keeping away from all kinds of dangers that threaten a child. In everyday life, people are less aware of the importance of limiting the age of marriage as stipulated in Law Number 1 of 1974 concerning Marriage.